Pattern of odontogenic infections at a tertiary hospital in tehran, iran: a 10-year retrospective study of 310 patients. - Fereydoun Pourdanesh; Nima Dehghani; Mohadese Azarsina; Zahra Malekhosein (Tehran University of Medical Sciences, 2013)
To retrospectively evaluate the treated cases with odontogenic abscess and identify the outcome of odontogenic infections, their characteristics and treatment modalities.This retrospective study was performed by collecting data from 310 patient records at the oral and maxillofacial surgery department of Taleghani hospital, Tehran, Iran from January 2001 to January 2011. The variables were age, gender, affected teeth, affected facial spaces, type of bacterial source, type of antibiotic therapy, previous medication, hospital stay, body temperature on admission and past medical history.The patients' ages were between 2 and 84 years and 62.6% of the patients with odontogenic infection were younger than 35 years old. Most of the patients had a body temperature of 37-37.5°C. The most involved teeth were mandibular third molar. Deciduous teeth contained 6.4% of the involved teeth, among which mandibular molars were the most involved. 24.3% of the patients were hospitalized for 4 days. Streptococci were the most detected bacterial strain. The most involved anatomic space was the buccal space and 22.5% of the cases had multi space involvement and 17 cases had Ludwig's angina. The most common used antibiotic regimens were penicillin G and metronidazole or cefazolin and metronidazole. The mortality rate was 1%, all of whom had Ludwig's angina.The main affected facial spaces were buccal and submandibular spaces. The most common used antibiotic was penicillin, proving its effectiveness in the treatment of jaw infections. Odontogenic abscesses are mostly related to the eruption of mandibular molars.